Protocol for maximising light signal of metallic magnetic calorimeters for neutrinoless double beta decay search. (6th July 2017) - Oh, S Y; Kim, G B; Kim, H L; Kim, I; Kim, S R; Lee, H J; Lee, M K; Kim, Y H
Abstract: We report on a systematic study for maximising the signal size of metallic magnetic calorimeters (MMCs) used for large-area light detectors operating at milli-Kelvin temperatures. These light detectors are to be used for phonon-scintillation detection using a scintillating crystal for rare event search experiments. The light detector is composed of a 2 inch wafer as an absorber for scintillation light from a crystal, and an MMC as its sensor. A systematic calculation for the expected signal size is made with different SQUID selections, Er concentrations of an MMC sensor, dimensions of the meander-shaped pick-up coil, field currents and operating temperatures. The optimisation study finds that more than five times larger signals can be achieved compared with that of a reference condition in which 90 eV root-mean-squared threshold is obtained. We also describe the inductance measurement for several MMC devices with different size of the pick-up coil to be applied for an optimal condition. This optimisation protocol is also valid for MMC applications of x-ray, alpha and beta spectroscopies.